Antidepressant Usage in Haemodialysis Patients: Evidence of Sub‐Optimal Practice Patterns. Issue 2 (12th February 2020) - Guirguis, Ayman; Chilcot, Joseph; Almond, Michael; Davenport, Andrew; Wellsted, David; Farrington, Ken
SUMMARY: Background: Depression is common in patients on haemodialysis and associated with adverse outcomes. Antidepressant use is widespread though evidence of efficacy is limited. Objectives: To study antidepressant management practices in patients on haemodialysis with reference to NICE guidelines on management of depression in adults with chronic physical health problems. Design: Prospective, multicentre, longitudinal cohort study with 6–15 month follow‐up. Participants: Patients on haemodialysis established on antidepressant medication. Measurements: Baseline assessment of mood was undertaken using Beck Depression Inventory (BDI‐II). Demographic, clinical and medication data were also collected. Changes in clinical and life circumstances and medication during follow‐up were recorded. At follow‐up, BDI‐II was reassessed and diagnostic psychiatric assessment undertaken. Results: Forty‐one patients were studied. General practitioners were the main prescribers (68%). Ten agents were in use, the commonest being Citalopram (39%). Doses were often suboptimal. At baseline, 30 patients had high BDI‐II scores (≥16) and 22 remained high at follow‐up. Eleven had BDI‐II < 16 at baseline. In five, this increased on follow‐up to ≥16. Sixteen patients (39%) had no medication review during follow‐up, 14 (34%) had a dose review, and 11 (27%) a medication change. On psychiatric assessment at follow‐up, eight patients had current major depressive disorder (MDD), seven recurrent and 20 evidence of past MDD. Six displayed no evidence of ever having MDD. Conclusions: Antidepressant management in patients on haemodialysis reflected poor drug selection, overprescription, under‐dosing and inadequate follow‐up suggesting sub‐optimal adherence to NICE guidelines. Most patients had high depression scores at follow‐up. Antidepressant use in haemodialysis requires reappraisal.